IMPLEMENTING CHARACTER VALUES FOR AUD THROUGH ACTIVITIESLOCAL WISDOM OUTING CLASS AT EDUTOURISM NDALEM KERTO - Pujiati, Ayu; Wulansari, Betty Yulia (Bunayya, 2023)
Outing class is a learning activity that can help children develop their various potentials, which can be used to adapt to their environment. This article aims to determine the cultivation of AUD character values through activities outing class local wisdom at Eduwisata Ndalem Kerto. This article uses a qualitative descriptive research method. The data collection techniques used in this research are direct communication and observation techniques. The data collection tools used in data collection are interview guidelines and observation guidelines. This research shows that based on the research results described above, local wisdom outing class activities can instill character values in young children. Learning outside the classroom with the system using class, which involves students directly with the natural surroundings, can support the development of aspects of learning outcomes such as aspects of social-emotional development and other elements so that children can have character values that match expectations. Learning through activities outing class Local wisdom in instilling character values provides opportunities for young children to increase awareness of protecting the environment, independence and understanding of the surrounding environment, increase children's knowledge about the surrounding environment, especially in recognizing animals and plants, and increase students' love and care for the environment.